The potential utilization of ultra-high performance concrete for bridge construction in Malaysia - Kasim, Norhidayu; Sulaiman, Mohd Rozaiman; Abu Taib, Kamarudin (IOP Publishing, 2019)
Ultra-High Performance Concrete (UHPC) is considered to be quite a new technology in Malaysia and it is still in the early stage of implementation as far as bridge design and construction in this country is concerned. Bridge Design Division, Public Works Department (PWD) has taken the initiative to study and to begin utilising UHPC in designing a 300 m long bridge crossing the Perak River between Kg. Seberang Manong (Kg Menglembu) to Kuala Kangsar, Perak. The purpose of using UHPC is to reduce the number of intermediate piers that need to be constructed within the river channel in order to minimize the impact of debris flow disaster. This will allow free flow of logs thus avoiding them from being trapped and could possibly damage the piers during flooding. The bridge has 5 spans with the longest span of 70 m in length that uses UHPC in its construction. In this bridge construction, it is quite impossible to use typical normal concrete commonly utilize in conventional concrete bridge project that normally limits the span length to only 40 m. This project is also a pilot project in PWD that uses Malaysia Civil Engineering Standard Method of Measurement (MYCESMM), replacing the current Malaysian Standard Method for Measurement of Civil Engineering Construction. The MYCESMM covers a wider range of civil engineering works. This project is expected to contribute towards delivering cost effective civil engineering projects through the adoption of best practices in the preparation of the bills of quantities (BQ). The successful application and construction of this pilot project will have a great prospect in encouraging more projects to use UHPC and MYCESMM in the upcoming projects in Malaysia